A plasmonically enhanced charge generation layer for tandem organic light emitting device - Yan, Fei (2013)
We studied silver nanoparticles (Ag NPs) as an n-type dopant in the charge generation connector of tandem organic light-emitting diodes. Due to the localized surface plasmonic resonance and quantum size effects, Ag NPs are more active and easy to lose electron comparing to bulk or film forms of Ag, and can work as excellent n-type dopant. For the tandem device with Ag NPs in the charge generation layer, the current efficiency is more than doubled and the driving voltage is less than twice compared to one single emission unit device.